Chronic stress is associated with reward and emotion-related eating behaviors in college students - Tuluhong, Muyesaier; Han, Pengfei (Frontiers in Nutrition, 2023)
Stress is related to altered olfactory perception and eating behaviors. The current study investigated the association between chronic stress, food reward and perception of food and non-food odors among college students. Sixty-one participants completed the Perceived Stress Scale (PSS) and the Brief Daily Stressors Screening Tool (BDSST). The detective threshold and suprathreshold perception (pleasantness, intensity and familiarity) of two food (chocolate, strawberry) odors and a non-food (rose) odor were measured. Food reward and macronutrient preference were measured using the computerized Leeds Food Preference Questionnaire and the Macronutrient and Taste Preference Ranking task, respectively. Reward-related eating, emotional eating and eating-related inhibitory control were measured by the DEBQ and the RED scales. Results showed that neither the perceived stress or the severity of daily life stressor exposure was related to odor sensitivity, however, the PSS score was significantly correlated with pleasantness for strawberry odor (r = 0.329, p = 0.013). Chronic stress was significantly correlated with emotional and reward-related eating behaviors (food preoccupation, lack of satiety, loss of control) measured by questionnaires. Moreover, the BDSST score was negatively correlated with subjective liking for low-calorie sweet foods (r = -0.46, p < 0.001). Together, our preliminary results suggest disassociated effect of chronic stress on odor perception and eating behaviors.